2020
DOI: 10.1186/s13047-020-00430-y
|View full text |Cite
|
Sign up to set email alerts
|

The New Zealand podiatry profession – a workforce in crisis?

Abstract: Background This is the first study to explore workforce data from the Podiatrists Board of New Zealand. The study analysed data from an online survey which New Zealand podiatrists complete as part of their application for an Annual Practising Certificate. Methods Survey responses between 2015 and 2019 were analysed. Data was related to work setting, employment status, work hours, location, professional affiliations, and number of graduates entering practice. Survey data was downloaded by a second party who p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…However, this response rate is approximately double that than the 8% reported by Quinton et al (15) in their similar study on diabetes-related foot assessment practices of podiatrists in Australia and slightly higher than Yuncken et al ( 29) who had a 10% response rate in a survey of podiatrists on the provision of education to people with diabetes. Additionally, previous research has identi ed that only a small percentage of the podiatry profession in NZ work primarily with people with diabetes on a daily basis (22%) (14) which may have contributed to the low response rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this response rate is approximately double that than the 8% reported by Quinton et al (15) in their similar study on diabetes-related foot assessment practices of podiatrists in Australia and slightly higher than Yuncken et al ( 29) who had a 10% response rate in a survey of podiatrists on the provision of education to people with diabetes. Additionally, previous research has identi ed that only a small percentage of the podiatry profession in NZ work primarily with people with diabetes on a daily basis (22%) (14) which may have contributed to the low response rate.…”
Section: Discussionmentioning
confidence: 99%
“…International guidelines also recognise that foot care provided by podiatrists is central to the prevention and management of DFD (13). In NZ, approximately 21% of podiatrists in NZ report they work with people with diabetes, including 80% of those working primarily in private practice and approximately 8% in public diabetes-related foot services (14). Foot services for people with diabetes is frequently split between preventative care for people at increased risk of DFD and specialist services for management of people with DFD.…”
Section: Introductionmentioning
confidence: 99%
“…However, this response rate is approximately double that than the 8% reported by Quinton et al [15] in their similar study on diabetes‐related foot assessment practices of podiatrists in Australia and slightly higher than Yuncken et al [29] who had a 10% response rate in a survey of podiatrists on the provision of education to people with diabetes. Additionally, previous research has identified that only a small percentage of the podiatry profession in NZ work primarily with people with diabetes on a daily basis (22%) [14] which may have contributed to the low response rate. Finally, approximately 50% of the respondents to this survey were from Auckland compared to regional areas of NZ.…”
Section: Discussionmentioning
confidence: 99%
“…International guidelines also recognise that foot care provided by podiatrists is central to the prevention and management of DFD [13]. In NZ, approximately 21% of podiatrists report they work with people with diabetes, including 80% of those working primarily in private practice and approximately 8% in public diabetes-related foot services with the remainder in research or higher education settings [14]. Foot services for people with diabetes is frequently split between preventative care for people at increased risk of DFD and specialist services for management of people with DFD.…”
Section: Introductionmentioning
confidence: 99%
“…There is currently limited research that has investigated the sustainability of the NZ podiatry workforce. Carroll et al, who analysed the NZ podiatry workforce data between 2015 and 2019 concluded that the NZ podiatry workforce is in crisis and demonstrated there were a smaller number of podiatrists working outside of major urban cities (Auckland, Wellington, Christchurch) [ 23 ]. However, this research provided no insight into the rural podiatry workforce.…”
Section: Introductionmentioning
confidence: 99%